Preparation method of anti-coking self-falling ceramic coating on heating surface of garbage incinerator

By forming a multi-layer composite coating on the heated surface of the waste incinerator, the problem that the heated surface of the waste incinerator is prone to coking in high temperature environments is solved, and efficient protection and self-falling functions are achieved, extending the service life of the equipment.

CN119530697AActive Publication Date: 2025-02-28SHANGQIU ZHONGDIAN ENVIRONMENTAL PROTECTION POWER GENERATION CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411492674.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The heated surface of the waste incinerator is prone to coking and ash accumulation in high temperature environments, resulting in unstable heat transfer, increased flue gas temperature and abnormal equipment operation. The existing anti-coking technology has problems such as frequent furnace shutdown, easy coating failure, incomplete cleaning and high maintenance costs.

Method used

After sandblasting, the nickel-based alloy coating is arc sprayed, and the first ceramic coating of liquid mixture of zirconia and alumina is brushed, and graphite paper and graphite sheets are laid thereon to form a multi-layer composite coating to ensure that the coating forms a dense protective layer at high temperature.

Benefits of technology

It effectively reduces the corrosion rate of coking, improves the adhesion and protection performance of the coating, extends the service life of the equipment, and maintains good corrosion resistance and self-repair ability under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530697A_ABST
    Figure CN119530697A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an anti-coking self-falling ceramic coating on a heating surface of a garbage incinerator, and belongs to the technical field of anti-slagging coatings. The method comprises the following operation steps: 1, performing sand blasting treatment on the heating surface of the garbage incinerator; 2, preparing a nickel-based alloy coating on the heated surface; 3, preparing a first ceramic coating on the nickel-based alloy coating; 4, graphite paper is laid on the first ceramic coating, and first round graphite flakes are evenly distributed and pasted on the first ceramic coating; 5, brushing a second ceramic coating in a gap between the adjacent round graphite sheets, and laying the graphite paper and a second layer of round graphite sheets according to the step (4); repeating the operation once to form a multi-layer composite coating consisting of three ceramic coatings and three graphite paper layers; 6, brushing an edge ceramic coating on the edge of the multi-layer composite coating to obtain an anti-coking self-falling ceramic coating; when the garbage incinerator runs, a compact protection layer is formed through reaction at the high temperature of 850 DEG C in the incinerator. The corrosion rate of the anti-coking self-falling ceramic coating is reduced to be 1t; and the thickness is 0.05 mm / year.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-slagging coating technology, and in particular relates to a method for preparing an anti-coking self-falling ceramic coating on a heating surface of a garbage incinerator. Background Art

[0002] With the acceleration of urbanization, the amount of garbage is increasing, and garbage disposal has become a very important task. At present, one of the commonly used garbage disposal methods is garbage incineration, which converts garbage into energy or reduces its volume by burning it at high temperature. In the garbage incineration process, the heating surface of the garbage incinerator operates for a long time in a high temperature environment, and is often eroded by corrosive gases, solid particles and high-temperature ash produced by the combustion of garbage, which is very easy to produce coking and ash accumulation, resulting in coking. The coking problem will affect the heat transfer stability, reduce the negative pressure, increase the flue gas temperature, cause abnormal temperature transmission problems and force the normal operation of the incinerator to stop. Severe cases will seriously affect the safe and stable operation of the boiler.

[0003] Existing anti-coking technologies for waste incinerators mainly include mechanical cleaning, traditional chemical protective coatings and soot blowing devices. Although they can improve the wear resistance and corrosion resistance of the equipment surface, facing the complex and harsh operating environment of waste incinerators, these methods still have defects such as frequent shutdowns, easy failure of coatings, incomplete cleaning and high maintenance costs.

[0004] In view of these problems, the present invention provides a ceramic coating technology for preventing coking and self-shedding, by forming a composite coating on the surface of the furnace wall. Summary of the invention

[0005] In order to achieve the goal of improving the anti-coking ability of the heating surface of a waste incinerator and making the coke fall off automatically, thereby improving the working efficiency and service life of the waste incinerator, the present invention provides a method for preparing an anti-coking self-falling ceramic coating for the heating surface of a waste incinerator.

[0006] A method for preparing a coking-proof self-shedding ceramic coating for a heating surface of a garbage incinerator, the operating steps are as follows: (1) Sand blasting The heating surface of the waste incinerator is a metal surface; the metal surface is sandblasted using quartz sand to make the roughness Ra value of the metal surface 3.5-6.0 μm, thereby obtaining a sandblasted metal surface; (2) Preparation of nickel-based alloy coating Arc spraying a nickel-based alloy material on a sandblasted metal surface to obtain a nickel-based alloy coating having a thickness greater than 100 μm; (3) Preparation of the first ceramic coating Applying a first ceramic coating on the nickel-based alloy coating; the material of the first ceramic coating is a liquid mixture of 50% to 70% by mass of zirconium oxide and 30% to 50% by mass of aluminum oxide; (4) Laying graphite paper (4.1) Before the first ceramic coating is dry, a layer of graphite paper is laid on the first ceramic coating; (4.2) Evenly pasting a first layer of graphite sheets on the graphite paper, the graphite sheets are round graphite sheets or square graphite sheets, and the first layer of graphite sheets are arranged in a crisscross pattern; (5) Preparation of multi-layer composite coatings After the graphite paper is dried, a second ceramic coating is applied by brushing in the gap area between adjacent graphite sheets of the first layer of graphite sheets; Laying a second layer of graphite paper on the second ceramic coating; evenly pasting a second layer of graphite sheets on the second layer of graphite paper; and the positions of adjacent layers of graphite sheets are staggered; Repeat step (5) once to finally form a multilayer composite coating of three layers of ceramic coating and three layers of graphite paper; (6) Preparation of edge ceramic coating After the multi-layer composite coating is dried, edge sealing treatment is performed on the edge of the multi-layer composite coating, and a layer of edge ceramic coating is applied to ensure that the edge of the graphite paper is not exposed to high-temperature flue gas, so as to obtain an anti-coking self-shedding ceramic coating; When the waste incinerator is in operation, the three-layer ceramic coating reacts with oxygen in the air at a high temperature of 850°C in the furnace to form a dense protective layer; The corrosion rate of the anti-coking self-shedding ceramic coating is reduced to <0.05mm / year in a continuous high temperature environment of 850°C; after 1000 hours of high temperature operation test, the adhesion of the coating is maintained at ≥10 MPa, the protective performance retention rate exceeds 95%, and the friction coefficient changes by less than 5%.

[0007] The further technical solution is as follows: In step (1), the particle size of the quartz sand is 0.6 to 0.8 mm; the sandblasting pressure is 0.5 to 0.7 MPa, and the processing time is 15 to 18 minutes.

[0008] In step (2), the material of the nickel-based alloy coating is 80Ni-20Cr solid solution strengthened high temperature alloy, and the thickness of the nickel-based alloy coating is 100-150 μm.

[0009] The material of the first ceramic coating is a liquid mixture of zirconium oxide and aluminum oxide, and the thickness of the first ceramic coating is 200-300 μm; the material and thickness of the three layers of ceramic coating are the same.

[0010] The preparation steps of the liquid mixture are as follows: (3.1) Mixing 50% to 70% by mass of zirconium oxide powder and 30% to 50% by mass of aluminum oxide powder in proportion to obtain a mixture; (3.2) Add deionized water or an alcohol dispersant in an amount of 30% to 50% of the mixture by mass, and disperse by mechanical stirring or ultrasonic dispersion to obtain a suspension; (3.3) The suspension is reacted in a high temperature and high pressure environment at a temperature of 200° C. and a pressure of 2 MPa for 2 hours to obtain a liquid mixture with good stability.

[0011] In step (3.2), the alcohol dispersant is ethanol or isopropanol.

[0012] In step (3.2), the mechanical stirring dispersion conditions are: rotation speed 800-1000 rpm, stirring time 30 minutes; the ultrasonic dispersion treatment conditions are: ultrasonic frequency 20-40 kHz, ultrasonic time 30 minutes.

[0013] In step (4.1), the thickness of the graphite paper is 0.2 mm.

[0014] In step (4.2), the diameter of the circular graphite sheet is 8 mm, and the spacing between adjacent circular graphite sheets is 20 mm.

[0015] In step (6), the thickness of the edge ceramic coating is 150 μm.

[0016] The beneficial technical effects of the present invention are embodied in the following aspects: 1. Anti-coking self-falling function: The present invention forms a micro-void structure by adding graphite sheets to the coating material. When the waste incinerator is running, the temperature of the heating surface is high, the coating expands unevenly locally, and the lubricity and thermal stability of the graphite sheets make the surface of the coating prone to cracks, causing the coke to fall off along with the cracks. This design effectively avoids the long-term accumulation of the coking layer.

[0017] 2. High temperature resistance and corrosion resistance: The ceramic coating has excellent high temperature resistance and can withstand temperatures up to 1400°C, and will not chemically decompose in high temperature environments. At the same time, the multi-layer composite structure of the nickel (Ni)-based alloy coating and the ceramic coating provides excellent corrosion resistance and can effectively resist the erosion of corrosive gases and solid particles generated by garbage combustion. Among them, the nickel (Ni)-based alloy coating has good oxidation resistance and corrosion resistance, which can effectively improve the adhesion strength between the ceramic coating and the metal substrate.

[0018] 3. Self-repairing ability: The present invention utilizes the thermal conductivity and lubricity of graphite paper, which helps to prevent high-temperature coking. The alternating structure of graphite paper and ceramic coating in the coating can expose the undamaged coating underneath when the local coating peels off, thus achieving a certain self-repairing effect and extending the service life of the coating.

[0019] 4. Through experimental data verification, experimental tests were conducted in a high-temperature corrosion environment. After the heating surface of the waste incinerator was coated with the coating technology of the present invention, the amount of coking was reduced by more than 60%, the self-shedding efficiency was increased by 40%, and the corrosion resistance was improved by about 40%. After 1,000 hours of high-temperature operation test, the coating still maintained good adhesion and protection performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of a waste incinerator.

[0021] Figure 2 for Figure 1 Schematic diagram of the composite coating on the middle furnace wall pipe.

[0022] Figure 3 for Figure 2 Schematic diagram of the arrangement of graphite discs on graphite paper. DETAILED DESCRIPTION

[0023] The present invention will be further described in detail below through embodiments in conjunction with the accompanying drawings. Example 1

[0024] The steps for preparing a self-shedding ceramic coating for the heating surface of a waste incinerator are as follows: (1) Sand blasting See also Figure 1 The heating surface of the waste incinerator, that is, the metal surface, was sandblasted with quartz sand with a particle size of 0.8 mm, the sandblasting pressure was 0.5 MPa, and the treatment time was 15 minutes. The roughness Ra of the metal surface after sandblasting was measured to be 4.5 μm, and a sandblasted metal surface was obtained.

[0025] (2) Preparation of nickel-based alloy coating A nickel (Ni)-based alloy coating with a thickness of 120 μm is sprayed on a sandblasted metal surface using an arc spraying device. The material of the nickel-based alloy coating is a 80Ni-20Cr solid solution strengthened high temperature alloy.

[0026] (3) Preparation of the first ceramic coating A first ceramic coating with a thickness of 250 μm is brushed on the nickel-based alloy coating.

[0027] The material of the first ceramic coating is a liquid mixture of zirconium oxide and aluminum oxide. The steps for preparing the liquid mixture are as follows: (3.1) 70% by mass of zirconium oxide powder and 30% by mass of aluminum oxide powder are mixed in proportion to obtain a mixture; (3.2) Add deionized water or an alcohol dispersant in an amount of 50% by mass of the mixture, and disperse under mechanical stirring at a speed of 1000 rpm for 30 minutes to obtain a suspension; (3.3) The suspension is reacted in a high temperature and high pressure environment at a temperature of 200° C. and a pressure of 2 MPa for 2 hours to obtain a liquid mixture with good stability.

[0028] (4) Laying graphite paper (4.1) Before the first ceramic coating is dried, a layer of graphite paper with a thickness of 0.2 mm is laid on the first ceramic coating; (4.2) See Figure 3 , the first layer of circular graphite sheets is evenly pasted on the graphite paper, the diameter of the circular graphite sheets is 8 mm, the spacing between adjacent circular graphite sheets is 20 mm, and they are arranged criss-cross.

[0029] (5) Preparation of multi-layer composite coatings After the graphite paper is dried, a second ceramic coating with a thickness of 250 μm is applied to the gap area between adjacent circular graphite sheets of the first layer of circular graphite sheets; when applying the second ceramic coating, the circular graphite sheets cannot be covered to ensure that the circular graphite sheets remain exposed.

[0030] A second layer of graphite paper is laid on the second ceramic coating; a second layer of circular graphite sheets is evenly adhered on the second layer of graphite paper; and the positions of the circular graphite sheets in adjacent layers are staggered.

[0031] Repeat step (5) once, see Figure 2 , and finally a multilayer composite coating of three layers of ceramic coating and three layers of graphite paper is formed.

[0032] (6) Preparation of edge ceramic coating After the multi-layer composite coating is dried, the edge of the multi-layer composite coating is sealed and a layer of 150 μm thick edge ceramic coating is applied to ensure that the edge of the graphite paper is not exposed to high-temperature flue gas, thereby obtaining an anti-coking self-shedding ceramic coating.

[0033] When the waste incinerator operates at 850°C, the three-layer ceramic coating reacts with the oxygen in the air at the high temperature of 850°C in the furnace to form a dense protective layer.

[0034] The anti-coking self-shedding ceramic coating of Example 1 has a corrosion rate reduced to <0.05 mm / year in a high temperature environment of 850°C; after 1000 hours of high temperature operation test, the adhesion of the coating is maintained at ≥10 MPa, the protective performance retention rate exceeds 95%, and the friction coefficient changes by less than 5%.

[0035] After 500 hours of high-temperature operation test of the incinerator, the amount of coking on the heating surface of the incinerator was reduced by 55%, and the self-shedding efficiency was increased by 35%. The anti-coking self-shedding ceramic coating remained intact at a maximum temperature of 1250°C without peeling or cracking, and the corrosion resistance was increased by 40%, effectively extending the operation time of the equipment. Example 2

[0036] The steps for preparing a self-shedding ceramic coating for the heating surface of a waste incinerator are as follows: (1) Sand blasting The heating surface of the waste incinerator, that is, the metal surface, was sandblasted with quartz sand with a particle size of 0.6 mm, the sandblasting pressure was 0.7 MPa, and the treatment time was 18 minutes. The roughness Ra of the metal surface after sandblasting was measured to be 5.0 μm, and a sandblasted metal surface was obtained.

[0037] (2) Preparation of nickel-based alloy coating A nickel (Ni)-based alloy coating with a thickness of 140 μm is sprayed on a sandblasted metal surface using an arc spraying device. The material of the nickel-based alloy coating is a 80Ni-20Cr solid solution strengthened high temperature alloy.

[0038] (3) Preparation of the first ceramic coating A first ceramic coating with a thickness of 220 μm is brushed on the nickel-based alloy coating.

[0039] The material of the first ceramic coating is a liquid mixture of zirconium oxide and aluminum oxide. The steps for preparing the liquid mixture are as follows: (3.1) 50% by mass of zirconium oxide powder and 50% by mass of aluminum oxide powder are mixed in proportion to obtain a mixture; (3.2) Add deionized water or alcohol dispersant in an amount of 30% by mass of the mixture, and disperse under ultrasonic waves at a frequency of 40 kHz for 30 minutes to obtain a suspension; (3.3) The suspension is reacted in a high temperature and high pressure environment at a temperature of 200° C. and a pressure of 2 MPa for 2 hours to obtain a liquid mixture with good stability.

[0040] (4) Laying graphite paper (4.1) Before the first ceramic coating is dried, a layer of graphite paper with a thickness of 0.3 mm is laid on the first ceramic coating; (4.2) The first layer of square graphite sheets is evenly pasted on the graphite paper. The length and width of the square graphite sheets are both 10 mm, the spacing between adjacent square graphite sheets is 25 mm, and they are arranged in a criss-cross pattern.

[0041] (5) Preparation of multi-layer composite coatings The operation of step (5) in this embodiment 2 is the same as the operation of step (5) in embodiment 1.

[0042] (6) Preparation of edge ceramic coating The operation of step (6) in this embodiment 2 is the same as the operation of step (6) in embodiment 1.

[0043] When the waste incinerator operates at 850°C, the three-layer ceramic coating reacts with the oxygen in the air at the high temperature of 850°C in the furnace to form a dense protective layer.

[0044] The corrosion rate of the anti-coking self-shedding ceramic coating of Example 2 is reduced to <0.05 mm / year in a high-temperature environment of 850°C; after 1000 hours of high-temperature operation test, the adhesion of the coating is maintained at ≥10 MPa, the protective performance retention rate exceeds 95%, and the friction coefficient changes by less than 5%.

[0045] After 1,000 hours of high-temperature operation test of the incinerator, the amount of coking on the heating surface of the incinerator was reduced by 60%, and the self-shedding efficiency was increased by 40%. The anti-coking self-shedding ceramic coating remained intact at a maximum temperature of 1,250°C without peeling or cracking, and the corrosion resistance was increased by 45%, effectively extending the operation time of the equipment.

[0046] It will be easily understood by those skilled in the art that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a coking-proof self-shedding ceramic coating for a heating surface of a waste incinerator, characterized in that: The steps are as follows: (1) Sand blasting The heating surface of the waste incinerator is a metal surface; the metal surface is sandblasted using quartz sand to make the roughness Ra value of the metal surface 3.5-6.0 μm, thereby obtaining a sandblasted metal surface; (2) Preparation of nickel-based alloy coating Arc spraying a nickel-based alloy material on a sandblasted metal surface to obtain a nickel-based alloy coating having a thickness greater than 100 μm; (3) Preparation of the first ceramic coating Applying a first ceramic coating on the nickel-based alloy coating; the material of the first ceramic coating is a liquid mixture of 50% to 70% by mass of zirconium oxide and 30% to 50% by mass of aluminum oxide; (4) Laying graphite paper (4.1) Before the first ceramic coating is dry, a layer of graphite paper is laid on the first ceramic coating; (4.2) Evenly pasting a first layer of graphite sheets on the graphite paper, the graphite sheets are round graphite sheets or square graphite sheets, and the first layer of graphite sheets are arranged in a crisscross pattern; (5) Preparation of multi-layer composite coatings After the graphite paper is dried, a second ceramic coating is applied by brushing in the gap area between adjacent graphite sheets of the first layer of graphite sheets; Laying a second layer of graphite paper on the second ceramic coating; evenly pasting a second layer of graphite sheets on the second layer of graphite paper; and the positions of adjacent layers of graphite sheets are staggered; Repeat step (5) once to finally form a multilayer composite coating of three layers of ceramic coating and three layers of graphite paper; (6) Preparation of edge ceramic coating After the multi-layer composite coating is dried, edge sealing treatment is performed on the edge of the multi-layer composite coating, and a layer of edge ceramic coating is applied to ensure that the edge of the graphite paper is not exposed to high-temperature flue gas, so as to obtain an anti-coking self-shedding ceramic coating; When the waste incinerator is in operation, the three-layer ceramic coating reacts with oxygen in the air at a high temperature of 850°C in the furnace to form a dense protective layer; The corrosion rate of the anti-coking self-shedding ceramic coating is reduced to <0.05 mm / year in a continuous high temperature environment of 850°C; after 1000 hours of high temperature operation test, the adhesion of the coating is maintained at ≥10 MPa, the protective performance retention rate exceeds 95%, and the friction coefficient changes by less than 5%.

2. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the quartz sand is 0.6 to 0.8 mm; the sandblasting pressure is 0.5 to 0.7 MPa, and the processing time is 15 to 18 minutes.

3. The preparation method according to claim 1, characterized in that: In step (2), the material of the nickel-based alloy coating is 80Ni-20Cr solid solution strengthened high temperature alloy, and the thickness of the nickel-based alloy coating is 100-150 μm.

4. The preparation method according to claim 1, characterized in that: The material of the first ceramic coating is a liquid mixture of zirconium oxide and aluminum oxide, and the thickness of the first ceramic coating is 200-300 μm; the material and thickness of the three layers of ceramic coating are the same.

5. The preparation method according to claim 4, characterized in that: The preparation steps of the liquid mixture are as follows: (3.1) Mixing 50% to 70% by mass of zirconium oxide powder and 30% to 50% by mass of aluminum oxide powder in proportion to obtain a mixture; (3.2) Add deionized water or an alcohol dispersant in an amount of 30% to 50% of the mixture by mass, and disperse by mechanical stirring or ultrasonic dispersion to obtain a suspension; (3.3) The suspension is reacted in a high temperature and high pressure environment at a temperature of 200° C. and a pressure of 2 MPa for 2 hours to obtain a liquid mixture with good stability.

6. The preparation method according to claim 5, characterized in that: In step (3.2), the alcohol dispersant is ethanol or isopropanol.

7. The preparation method according to claim 5, characterized in that: In step (3.2), the mechanical stirring dispersion conditions are: rotation speed 800-1000 rpm, stirring time 30 minutes; the ultrasonic dispersion treatment conditions are: ultrasonic frequency 20-40 kHz, ultrasonic time 30 minutes.

8. The preparation method according to claim 1, characterized in that: In step (4.1), the thickness of the graphite paper is 0.2 mm.

9. The preparation method according to claim 1, characterized in that: In step (4.2), the diameter of the circular graphite sheet is 8 mm, and the spacing between adjacent circular graphite sheets is 20 mm.

10. The preparation method according to claim 1, characterized in that: In step (6), the thickness of the edge ceramic coating is 150 μm.

Citation Information

Patent Citations

  • Composite heat conduction sheet, preparation method thereof and heat dissipation piece

    CN110933899A

  • Preparation method of anti-coking composite ceramic coating for power station boiler

    CN114525466A

  • Corrosion-resistant anti-coking garbage furnace heating surface structure protective coating

    CN209944355U

  • Anti-corrosion and Anti-coking ceramic coating with easy state identification for coal-fired boiler and preparation method thereof

    US20230060480A1